Reproducibility in research - Vivian Siegel (The Company of Biologists, 2011)
Summary Progress in biomedical research depends in part on being able to build on the findings of other researchers - and thereby on being able to apply others' methods to your own research. However, most of us have struggled to understand how to repeat or adapt another researcher's study because of minimal or missing details in the Methods section of a published paper. In expensive and complex experiments involving animal models, clear descriptions of the methods are particularly important. In this and the accompanying Editorial in this issue, we discuss how crucial the Methods section is to the integrity and utility of a biomedical research paper, and encourage researchers working with animal models to follow the recently released ARRIVE guidelines when preparing their studies for publication.